Petrogenesis of granitoids and associated xenoliths in the early Paleozoic Baoxu and Enping plutons, South China: Implications for the evolution of the Wuyi-Yunkai intracontinental orogen. (1st May 2018) - Yu, Yang; Huang, Xiao-Long; Sun, Min; He, Peng-Li
Graphical abstract: Highlights: The Wuyi-Yunkai intracontinental orogeny resulted in crustal thickening. The Wuyi-Yunkai intracontinental orogen uplifted firstly along an ancient suture zone. Mafic magmas emplaced mainly near an ancient suture zone during orogenic collapse. Abstract: The early Paleozoic Wuyi-Yunkai orogen was associated with extensive felsic magmatic activities and the orogenic core was mainly distributed in the Yunkai and Wugong domains located in the western Cathaysia block and in the Wuyi domain located in the central part of the Cathaysia block. In order to investigate the evolution of the Wuyi-Yunkai orogen, elemental and Sr-Nd isotopic analyses were performed for granites from the Baoxu pluton in the Yunkai domain and from the Enping pluton in the central part of the Cathaysia block. The Baoxu pluton consists of biotite granite with abundant xenoliths of gneissic granite, granodiorite and diorite, and the Enping pluton is mainly composed of massive granodiorite. Biotite granites (441 ± 5 Ma) and gneissic granite xenolith (443 ± 4 Ma) of the Baoxu pluton are all weakly peraluminous (A/CNK = 1.05–1.10). They show high Sr/Y and La/Yb ratios and have negative bulk-rock εNd (t) values (−7.0 to −4.4), which are similar to coeval gneissic S-type granites in the Yunkai domain and were probably derived from dehydration melting of a sedimentary source with garnet residue in the source. Granodiorites (429 ± 3 Ma) from Enping and granodiorite xenolith (442 ± 4 Ma) from Baoxu are metaluminous and have REE patterns with enriched light REE and flat middle to heavy REE, possibly generated by the dehydration melting of an igneous basement at middle to lower crustal level. Diorite xenolith from Baoxu is ultrapotassic (K2 O = 4.9 wt%), has high contents of MgO (7.0 wt%), Cr (379 ppm) and Ni (171 ppm) and shows pronounced negative Nb, Ta and Ti anomalies. This xenolith also has negative εNd (t) value (−3.6) and low Rb/Ba and high Ba/Sr ratios, and is thus interpreted to be derived from an enriched lithospheric mantle with the breakdown of phlogopite. Early Paleozoic I- and S-type granites in the Wuyi-Yunkai orogen mostly have negative εNd (t) values and do not have juvenile components, consistent with genesis by an intracontinental orogenic event. These early Paleozoic granites occur near the ancient suture zone between the Yangtze and Cathaysia blocks and have high La/Yb and Sr/Y ratios, likely due to the existence of residual garnet in the source, suggesting the thickened crust at ca. 440 Ma. The 450–440 Ma gneissic S-type granites near the suture zone are earlier than those in the central part of the Cathaysia block (∼430 Ma). The crustal thickening along the ancient suture zone at 440 Ma propagated into the central part of the Cathaysia block as evidenced by the 430 Ma granites. Early Paleozoic I-type granites near the suture zone clearly show involvement of significant mantle-derived materials, in contrast to granites in the central part of the Cathaysia block. The ancient suture zone may have acted as channels for the emplacement of mafic magmas during the collapse of an intracontinental orogen.